Vague pension future: Empirical evidence from the Israeli radical privatized market - Ishay Wolf; Smadar Levi (Journal of Risk and Financial Management, 2022)
We examine the future benefits of the Israeli privatized pension system, which is considered as a model of transition to funded pension systems worldwide. This research is based on an extensive database obtained from one of the largest traditional private funds in the market. The results paint a concerning picture regarding the adequacy of benefits and quality of life in old age. Israel's radical privatized pension model signals a warning to other nations. We show that, even with high returns, most individuals cannot handle the magnitude of financial and labor risks accumulated during their career and retirement. We recommend more balanced government intervention as well as the use of risk-sharing mechanisms such as providing minimum pension guarantee and strengthening the unfunded social security pillar.
Keywords: 650; public policy; funded pension scheme; Israel; minimum pension guarantee; poverty; social security